2016
DOI: 10.1002/eji.201646300
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal‐associated invariant T cells are reduced and functionally immature in the peripheral blood of primary Sjögren's syndrome patients

Abstract: The frequencies, immunophenotype, and function of mucosal-associated invariant T (MAIT) cells were studied in patients with primary Sjögren syndrome (pSS) and healthy controls. MAIT cells were significantly decreased in the peripheral blood (PB) of patients with pSS. Vα7.2 MAIT cells were detected in the salivary gland tissue from pSS patients, but not in controls, indicating that the reduction of MAIT cells in PB might be due to migration into the target tissue. Furthermore, the residual peripheral blood MAIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…The altered function of MAIT cells in pSS SG might lead to the dysregulation of the local immune responses, triggering autoimmune damage of the glandular tissue and development of sicca symptoms. Although Wang et al showed a lower level of MAIT-cell activation with reduced expression of CD69 and CD154 (CD40L) and a lower production of TNF and IFN-γ, a precise functional characterization of MAIT cells in pSS patients is still missing [1].…”
Section: Il-17 Polarization Of Mait Cells Is Derived From the Activatmentioning
confidence: 99%
“…The altered function of MAIT cells in pSS SG might lead to the dysregulation of the local immune responses, triggering autoimmune damage of the glandular tissue and development of sicca symptoms. Although Wang et al showed a lower level of MAIT-cell activation with reduced expression of CD69 and CD154 (CD40L) and a lower production of TNF and IFN-γ, a precise functional characterization of MAIT cells in pSS patients is still missing [1].…”
Section: Il-17 Polarization Of Mait Cells Is Derived From the Activatmentioning
confidence: 99%
“…Functional analysis suggested that MAIT cells from pSS patients produced less cytokines, TNF and IFNc, as compared to healthy controls (PMA iono). 49 A second study confirmed the reduction of blood MAIT cells in pSS patients and further showed an enrichment of IL-17 polarized MAIT cells. 50 In vitro stimulation of purified blood MAIT cells from pSS patients with IL-7 and IL-23, two cytokines involved in pSS pathogenesis, enhanced their level of IL-17 mRNA.…”
Section: Sj €mentioning
confidence: 73%
“…However, this modification might reflect an increased proportion of Vα7.2 + T cells that are not MAIT cells (no MR1‐tetramer staining were performed). Functional analysis suggested that MAIT cells from pSS patients produced less cytokines, TNF and IFNγ, as compared to healthy controls (PMA iono) . A second study confirmed the reduction of blood MAIT cells in pSS patients and further showed an enrichment of IL‐17 polarized MAIT cells .…”
Section: Sjögren's Syndromementioning
confidence: 73%
See 2 more Smart Citations